Stock Liquidity, Financial Report Quality, Wedge, and The Propensity to Pay Dividend - Rahmat Setiawan; Nova Christiana; Sanju Kumar Singh (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2019)
This research examined the effect of stock liquidity on the propensity to pay dividend for 254 Indonesian public listed firms during the period of l 2011 and 2015. Stock liquidity implies transparency level and serves as market monitor for management performance in using the cash flow. Furthermore, this research examines the impact of stock liquidity on dividend payment in the presence of agency conflicts using agency proxies, wedge and government ownership. This paper employed multivariate probit regression. The baseline model has controlled for time in-variant and industry sectors. Robustness checks are employed to present consistent result for other stock liquidity measures. The results confirm the predicted dividend model outcome and prove the contradiction in dividend signaling theory.